Marketing Public Relations Sebagai Business Representative Dalam Meningkatkan Penjualan Dengan Metode B2B - Angela, Nathania Dea; Wijaya, Lina Sinatra (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This journal reviews the marketing public relations strategy used to increase sales with the B2B method at PT Helios Informatika Nusantara. This study aims to know and understand the role and strategy of marketing public relations as a business representative in the B2B method. This type of research is descriptive qualitative research with a constructivism paradigm. Regarding the research instruments are interviews, observation, and documentation. The data source for this research uses various documentation owned by the company in conducting online and offline events because these two types of marketing are needed to get leads for the company. Then for data validation, this research uses triangulation. The combined data is seen clearly and in detail regarding the phenomena and problems raised in the study. The results of this study indicate that the marketing strategy used in the B2B method at Helios can run through two stages, digitally and non-digitally, and the various techniques developed within it will support the company sales increase process.